PREPARATION OF FLOORS IN EARTHQUAKE AREAS AND DESIGN OF LOAD-BEARING STRUCTURES IN EARTHQUAKE-PROBENT AREAS (Web of Teachers: Inderscience Research, 2024)
According to the article, in order to build buildings in earthquake-prone areas, first of all, the composition of the soil should be studied. Earthquakes in rocky areas are poorly known when seismic force is calculated in 8–9-point zones. Seymik is checked with special devices in the study of regions.